Analisis Pengukuran Produktivitas Menggunakan Metode Marvin E. Mundel Pada Usaha Konveksi Eli Collection - Muhammad Zulham; Novi Marlyana (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Eli Collection convection business is a medium-sized business engaged in the convection sector producing various types of sports pants including training pants, shorts, and chinos. The production process of this business applies a make-to-order system. The business has a number of order requests, but some businesses are still unable to fulfill these requests. Therefore, productivity calculations are needed. The author uses the Marvin E. Mundel method for productivity calculations. In January as the base or base period and finally obtained the results that the partial productivity index fluctuated after being compared with the base period at a percentage of 100%. The highest raw material productivity index occurred in April at 128.8% and the lowest in May at 81.51%. The highest labor productivity index occurred in April at 109.12% and the lowest in June at 93.78%. The highest energy productivity index occurred in May at 126.55% and the lowest in April at 87.84%. The highest machinery and production equipment depreciation productivity index occurred in April at 111.76% and the lowest in June at 91.71%. The highest machine maintenance productivity index occurred in May at 530.23%, and the lowest in September at 33.1%. The productivity index calculations identified several factors that contributed most to the problem, including raw material, labor, machinery, and energy productivity. This was due to the greater decline in these productivity indexes.